2018
DOI: 10.1186/s12890-018-0742-1
|View full text |Cite
|
Sign up to set email alerts
|

Metallic small y stent placement at primary right carina for bronchial disease

Abstract: BackgroundMetallic large Y stent placement has been used mainly for airway disease around the main carina. However, few studies have reported this treatment for bronchial disease around the primary right carina.MethodsTwenty-eight patients were treated by small y stent. All stents were custom-designed and placed under fluoroscopic guidance. Clinical and imaging data were analyzed retrospectively.ResultsThirty-one stents were successfully inserted in 28 patients. Twenty-five patients succeed at the first attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…And the complications are similar among two types of the stents in most conditions which included migration, granulation, diminished mucociliary clearance and patient intolerance. Previous studies have reported the complication rate of 16.1-40.9% in re-establishment of airway with Y stents and 31.3-44.4% with SEMS (15)(16)(17).…”
Section: Discussionmentioning
confidence: 97%
“…And the complications are similar among two types of the stents in most conditions which included migration, granulation, diminished mucociliary clearance and patient intolerance. Previous studies have reported the complication rate of 16.1-40.9% in re-establishment of airway with Y stents and 31.3-44.4% with SEMS (15)(16)(17).…”
Section: Discussionmentioning
confidence: 97%
“…Different types of airway stents have been studied, including Y silicone airway stents [911] and self-expanding metallic airway stents [1217]. The silicone airway stent is one of the most common types of stent, and often shows advantages of easy removal, durability and low cost when compared with metallic stents [7, 9, 1820]. Silicone Y-stents have been inserted in the main carina and the right upper carina [7, 11, 2123], and the secondary left carina [8, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, metallic Y stents are available and used clinically. Individualized metallic Y stents can be produced upon request and are designed to fit on the main carina [9]. Besides, silicone stent can be placed under a rigid bronchoscope by a respiratory physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a larger radial/bending strength, correlated with higher contact force between stent and the lesion, could mitigate the migration of a straight stent [24]. The concern of migration was much relieved for both the J-and Y-shaped stents, because each junction configuration, itself, constrained the migration of the stent in a bifurcated lesion [25]. The fatigue behavior of the J-shaped and Yshaped stents might be essential due to inspiration and expiration following stenting [26].…”
Section: Discussionmentioning
confidence: 99%